Komposisi Kimia Tepung dan Pati Umbi Ganyong dan Garut Koleksi Kebun Sumber Daya Genetik Natar, Lampung Selatan - Novitasari, Erliana; Ernawati, Rr; Lasmono, Agung; Ramadhani, Tika Nafiah; Meithasari, Dian (Seminar Nasional Lahan Suboptimal, 2022)
Chemical composition of canna and arrowroot flour and starch cultivated in genetic resources garden collection in Natar, South Lampung. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 929-936. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to determine the chemical composition of flour and starch made from canna tubers and arrowroot tubers. Processing tubers into flour or starch provides opportunities for wider utilization and longer storage. The tuber flour was processed using the dry method while the tuber starch was processed using the wet method. Characterization of chemical composition includes proximate analysis consisting of moisture content, ash content, crude fiber, protein, fat and carbohydrates as well as whiteness. The fat and protein content of canna tuber flour (0.93% and 2.30%) and arrowroot (0.59% and 3.50%) were slightly higher than the fat content of canna tuber starch (0.89% and 1, respectively). 2%) and arrowroot (0.39% and 1.26%). The yield and whiteness of canna and arrowroot flour and starch produced in this study were low.